Debt, bargaining, and credibility in firm–supplier relationships - Hennessy, Christopher A.; Livdan, Dmitry (Journal of Financial Economics, 2009)
We examine optimal leverage for a downstream firm relying on implicit (self-enforcing) contracts with a supplier. Performing a leveraged recapitalization prior to bargaining increases the firm's share of total surplus. However, the resulting debt overhang limits the range of credible bonuses, resulting in low input quality. Optimal financial structure trades off bargaining benefits of debt with inefficiency resulting from overhang. Consistent with empirical evidence, the model predicts that leverage increases with supplier bargaining power (e.g., unionization rates) and decreases with utilization of non-verifiable inputs (e.g., human capital).